Position of language: case of the Slovene language - Novak-Lukanovič, Sonja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article stresses the symbolic and communicational meaning of the language and analyses the position of the Slovene language in different historical periods, as well as the role of the Slovene language in the formation of the state. The Slovene language as the constitutionally determined official language since the Vidovdan Constitution (1921 ) till today is mentioned. The contact of the Slovene language with minority languages in the ethnically mixed areas is presented, and due to the processes of globalization also the contact with other languages. Emphasised is the role of the Office for the Slovene Language, and standpoints for the implementation of the special law regulating the status of the Slovene language in Slovenia are stated. The article concludes that the basic dilemma of the protection of the Slovene language remains outside the jurisprudence. Even though the official language is protected by the Constitution and special law, it cannot be efficiently protected unless it is a generally accepted value, firmly anchored in every individual's value system.
Keywords: Slovene; slovenščina; zakonodaja; zaščita manjšin; jezikovna politika; vloga jezika; jeziki v stiku